ENT 530 Case Study: Alya's Dessert / Nur Atirah Zahrah Noor Alamshah - Noor Alamshah, Nur Atirah Zahrah (2021)
Alya’s Dessert is a home-based business that focus in selling Shepherd Pies, offering decently priced yet delicious pies to the customer. This small business was started by Miss Nur Alya’s mother in 2018 after she had realized that both of her children, who during that time was UiTM students, are neglecting to eat healthy meals due to their busy schedules, hence they also fail to look after their health. After being told by Miss Alya and her brother’s friends about their interest in purchasing the pies, the mother of four agreed to sell the pies through the two siblings, who now acted as her business agents. The reason for why she chose Shepherd pie is because of its’ simple yet satisfying nourishment and likeability among teenagers and young adults. She would gather orders through her children on that day’s morning and send the freshly baked pies during the evening, in hope that each of her customers can look forward to eating their pies after an exhausting day filled with straining classes. Alya’s Dessert prepare fresh shepherd pies in a single proportion daily. By the time it reaches the customer’s hand, it would be warm to eat and require no heating up. The shepherd pie is ideal for any occasions and at any time as it could last for a couple of hours. This is perfect for university students who has rigorous and busy routine. Miss Alya’s mother would like her customers to see her food as a comfort food to remind them of positive times of eating with loved ones. Due to the seriousness of the current pandemic, Alya’s Dessert only caters to smaller batches of orders, focusing on close friends and relatives or repeating customers. However, Miss Alya had shared her interest in expanding this small business in the unforeseeable future.